The Consideration of the Ptun Judge Number 295/G/2019/Ptun.Mdn Re-garding the Settlement of Disputes Regarding Incomplete Requirements for the Election of Village Heads in Bargottopong Jae Village from the Perspec-tive of Fiqh Siyasah Qhadaiyah - Nauli, Ahmad Arif; Siregar, Ramadhan Syahmedi (IHSA Institute, 2025)
Indonesia is a unitary state, where villages have the authority to regulate and manage the interests of their communities in accordance with local customs and traditions recognized in the national government system. The purpose of this study is to understand how the judge's considerations in the PTUN Decision Number 295/G/2019/PTUN.MDN regarding the dispute over incomplete requirements in the election of village heads in Bargottopong Jae Village, North Padang Lawas Regency, are viewed from the perspective of fiqh siyasah qadha'iyyah (Islamic judicial law). The research method used is normative law. The results of the study indicate that the case of the village head election dispute in Bargottopong Jae Village shows the importance of law enforcement and justice in local government, where the Medan PTUN canceled the candidacy of Agussalim Siregar for violating Article 39 of Law No. 6 of 2014 concerning the term limits of the village head. From the perspective of siyasah fiqh, this decision reflects the principles of justice (al-'ilah), public benefit (al-maslahah), and deliberation (al-syura), and shows the role of the court as a control against deviations in power in order to maintain democracy and leadership integrity